2020
DOI: 10.1002/adhm.201901630
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Neurons form a Functional Neuronal Network in a 3D Printed Reinforced Matrix

Abstract: Impairments in neuronal circuits underly multiple neurodevelopmental and neurodegenerative disorders. 3D cell culture models enhance the complexity of in vitro systems and provide a microenvironment closer to the native situation than with 2D cultures. Such novel model systems will allow the assessment of neuronal network formation and their dysfunction under disease conditions. Here, mouse cortical neurons are cultured from embryonic day E17 within in a fiber‐reinforced matrix. A soft Matrigel with a shear mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…This is one approach to shift the biofabrication window to softer hydrogels and matrices while retaining handling or biomechanical requirements. [35,38,42,57] Such composite approaches, reinforcing MEW-fabricated PCL scaffolds into hydrogels that include gelatin methacryloyl (GelMA), show promising results regarding the stiffness increasing by up to 54-fold. [42] In this fiber-reinforced composite study, embedded human chondrocytes showed good viability and retained their roundish morphology, showing compatibility in terms of stiffness and biological cues for cartilage applications.…”
Section: Soft Network Compositesmentioning
confidence: 99%
See 3 more Smart Citations
“…This is one approach to shift the biofabrication window to softer hydrogels and matrices while retaining handling or biomechanical requirements. [35,38,42,57] Such composite approaches, reinforcing MEW-fabricated PCL scaffolds into hydrogels that include gelatin methacryloyl (GelMA), show promising results regarding the stiffness increasing by up to 54-fold. [42] In this fiber-reinforced composite study, embedded human chondrocytes showed good viability and retained their roundish morphology, showing compatibility in terms of stiffness and biological cues for cartilage applications.…”
Section: Soft Network Compositesmentioning
confidence: 99%
“…Finally, to provide 3D neuronal cell culture models with a weak matrix microenvironment closer to the native tissue, MEW fabricated scaffolds were embedded into Matrigel. [38,41] Those reinforced scaffolds within the Matrigel improved the mechanical properties and therefore the handling of the delicate constructs. [38,41] Another approach to mimic native tissue and its composition was demonstrated by using orthogonal microfiber scaffolds embedded into compressed collagen to design an artificial cornea.…”
Section: Soft Network Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…The laminin-rich property can fulfill an essential component of the brain. Laminin is one of the abundant proteins in the brain ECM; it promotes cell proliferation and differentiation, and supports neural cell attachment [ 101 , 102 , 103 ].…”
Section: Materials For Neural Mps Designmentioning
confidence: 99%